El oficio del traductor - Ferlan, Jaquelina (2018)
The representation is a staging. It i cvcs to remake it present with images and words. It is translation.Translation is an everyday essential communication act, an act to understand the world, to make it intelligible and communicable, located at the meeting of language, culture and identity.Translating is styling words by asking thousands of questions. The image, considered in modernity as a mere illustration that accompanied the word, it is revalue here as a grafh condition, capable of forming and informing, to (con) forming a text.